Development of Marine and Coastal Tourism Based on Blue Economy - Dimas Tegar; Raja Oloan Saut Gurning (International Journal of Marine Engineering Innovation and Research, 2018)
Marine and coastal tourism as one of the largest segments of the maritime economy sector, as well as the largest component of the tourism industry, often leads to controversy over environmental  impact  and  compatibility  with  other  human  activities.  The  application  of economic  and  tourism concepts  that  are  oriented  towards  environmental  conservation  and natural resources is one option to overcome the problem. The Blue Economy concept offers an economic concept based on ecosystem principles, where the development will not only generate economic growth but also ensure ecological and social sustainability. In addition, the concept of ecotourism also offers a tourism activity that prioritizes aspects of nature conservation and improving the welfare of the community